2011
DOI: 10.2151/sola.2011-024
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Plane Displacement Height in a Highly Built-Up Area of Tokyo

Abstract: The zero-plane displacement height d was evaluated in downtown Tokyo by the two independent methods of temperature variance and scintillometer heat flux. Regardless of the method, d exceeds the area-weighted average building height. This may be because d, which represents the point of effect for wind drag, is elevated by some tall buildings that jut above others. The areaweighted average building height would then be unsuitable as a geometrical index of urban canopies with large height variations. Thus, the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…This conclusion is supported by numerical and physical experiments (e.g. Jiang et al 2008;Hagishima et al 2009;Zaki et al 2011;Millward-Hopkins et al 2011;Tanaka et al 2011;Kanda et al 2013) indicating the taller roughness elements in a heterogeneous mix exert a disproportionate amount of drag on the flow (Xie et al 2008;Mohammad et al 2015b) lifting the drag-profile centroid (Jackson 1981) above z = H av . The results verify Kanda et al's (2013) proposition that the maximum height (H max ) is a more suitable scaling parameter for z d and the standard deviation of the roughnesselement height (σ H ) (also used by Millward-Hopkins et al 2011) is useful to parametrize roughness-element height heterogeneity.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This conclusion is supported by numerical and physical experiments (e.g. Jiang et al 2008;Hagishima et al 2009;Zaki et al 2011;Millward-Hopkins et al 2011;Tanaka et al 2011;Kanda et al 2013) indicating the taller roughness elements in a heterogeneous mix exert a disproportionate amount of drag on the flow (Xie et al 2008;Mohammad et al 2015b) lifting the drag-profile centroid (Jackson 1981) above z = H av . The results verify Kanda et al's (2013) proposition that the maximum height (H max ) is a more suitable scaling parameter for z d and the standard deviation of the roughnesselement height (σ H ) (also used by Millward-Hopkins et al 2011) is useful to parametrize roughness-element height heterogeneity.…”
Section: Discussionmentioning
confidence: 63%
“…5a-c). Previous studies found z d may be larger than H av in urban areas using both the temperature (Grimmond et al 1998(Grimmond et al , 2002Feigenwinter et al 1999;Kanda et al 2002;Christen 2005;Chang and Huynh 2007;Tanaka et al 2011) and velocity (Tsuang et al 2003) Table 3). …”
Section: Z D Determined By Anemometric Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…As with previous applications, z d determined using the temperature and wind variance methods at both sites indicates z d is larger than H av (e.g. Grimmond et al 1998 , 2002 , Feigenwinter et al 1999 , Kanda et al 2002 , Tsuang et al 2003 , Christen 2005 , Chang and Huynh 2007 , Tanaka et al 2011 , Kent et al 2017b ). Additionally, morphometric z d results are consistently smaller than anemometric results.…”
Section: Resultssupporting
confidence: 73%
“…For example, [8] used catastral databases, whereas [14] applied a characterization of buildings in urban terrains. In particular, [84] estimated d in Tokyo considering buildings of different heights. Most of these methods require costly field works.…”
Section: Land Cover Databasesmentioning
confidence: 99%